Pandemic Governance in Japan and the United States: The Control-Tower Metaphor - Michael R. Reich (Health Systems & Reform, 2020)
A comparative assessment of pandemic governance in Japan and the United States helps explain the strikingly different shapes of the Covid-19 pandemic in these two countries. Japan has more successfully managed the pandemic compared to the striking failure of the US response. This paper uses the metaphor of the control tower of an airport to examine four aspects of pandemic governance: (1) the culture of the control tower, showing strikingly different cultures of mask-wearing; (2) the social value context of the control tower, reflecting a greater tendency in Japan for people to follow government advice, compared to the US libertarian values of emphasizing personal liberty and disregarding official advice; (3) the role of national leadership, especially who is sitting in the control tower making decisions, with Prime Minister Abe largely taking responsibility while President Trump effectively left decisions up to markets and individual states; and (4) the use and clarity of information provided by control-tower authorities, showing greater clarity and consistency in Japan compared to the confused and contradictory messages in the US. These differences in control-tower governance have had marked effects on the pandemic responses of the two countries and have important implications for sustaining democratic traditions.